2018
DOI: 10.1111/jdv.15095
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary prevention of skin cancer in mountain guides: attitude and motivation for or against participation

Abstract: Awareness of prevention strategies recommended by the scientific community is low among affected occupationally high-risk mountain guide populations. Understanding the specific needs of this high-risk group is essential for the development of sustainable awareness and prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
0
14
0
2
Order By: Relevance
“…Using relevant literature and the manual for conducting qualitative interviews published by Helfferich, a topic guide consisting of open‐ended questions was developed to reflect the primary research objective (Table ). In developing this topic guide, we followed a pragmatic approach and did not prespecify a theory or model.…”
Section: Methodsmentioning
confidence: 99%
“…Using relevant literature and the manual for conducting qualitative interviews published by Helfferich, a topic guide consisting of open‐ended questions was developed to reflect the primary research objective (Table ). In developing this topic guide, we followed a pragmatic approach and did not prespecify a theory or model.…”
Section: Methodsmentioning
confidence: 99%
“…Outdoor workers from different occupational settings had a fundamental understanding of sun protection methods and of UVR as a key risk factor for KC. 16,[35][36][37][38][39][40] However, agricultural workers from Italy and Latino migrant farmworkers did not have appropriate awareness. 41,42 Twenty-two per cent of Latino migrant farmworkers in the USA had never heard of skin cancer before.…”
Section: Sun-related Knowledge and Awarenessmentioning
confidence: 99%
“…2). 9,16,[36][37][38][39][40][41][42][43][44][45][46][47][63][64][65][66][67][68][69][70][71][72] About one-third of mountain guides from Germany used sunscreen with a SPF < 30, 37,63 and only a small share of German outdoor workers checked the SPF of sunscreen before applying it. 9 Twenty-eight per cent to 86% of different medical professionals applied sunscreen during sun exposure.…”
Section: Sun Protection Behaviourmentioning
confidence: 99%
“…shown that utilization of such strategies is not highly prevalent (21)(22)(23), particularly among individuals who spend a lot of time outdoors (24)(25)(26)(27).…”
mentioning
confidence: 99%